Molecular characterization of Paenibacillus antarcticus IPAC21, a bioemulsifier producer isolated from Antarctic soil - de Lemos, Ericka Arregue; Procópio, Luciano; da Mota, Fabio Faria; Jurelevicius, Diogo; Rosado, Alexandre Soares; Seldin, Lucy (Frontiers in Microbiology, 2023)
Paenibacillus antarcticus IPAC21, an endospore-forming and bioemulsifier-producing strain, was isolated from King George Island, Antarctica. As psychrotolerant/psychrophilic bacteria can be considered promising sources for novel products such as bioactive compounds and other industrially relevant substances/compounds, the IPAC21 genome was sequenced using Illumina Hi-seq, and a search for genes related to the production of bioemulsifiers and other metabolic pathways was performed. The IPAC21 strain has a genome of 5,505,124 bp and a G+C content of 40.5%. Genes related to the biosynthesis of exopolysaccharides, such as the gene that encodes the extracellular enzyme levansucrase responsible for the synthesis of levan, the 2,3-butanediol pathway, PTS sugar transporters, cold-shock proteins, and chaperones were found in its genome. IPAC21 cell-free supernatants obtained after cell growth in trypticase soy broth at different temperatures were evaluated for bioemulsifier production by the emulsification index (EI) using hexadecane, kerosene and diesel. EI values higher than 50% were obtained using the three oil derivatives when IPAC21 was grown at 28°C. The bioemulsifier produced by P. antarcticus IPAC21 was stable at different NaCl concentrations, low temperatures and pH values, suggesting its potential use in lower and moderate temperature processes in the petroleum industry.